2015
DOI: 10.1016/j.ijgo.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the placental levels of oxidative stress markers in pre‐eclampsia

Abstract: Pre-eclampsia might be characterized by differential placental oxidative stress and antioxidant enzyme activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 24 publications
(32 reference statements)
0
26
1
3
Order By: Relevance
“…In our earlier study, we have reported higher oxidative stress indicated by the increased MDA levels in all regions of preterm preeclampsia group as compared to the normotensive control group [24]. Studies from our department and by others suggest that there is a presence of higher oxidative stress in women with preeclampsia and in preeclampsia placenta [29,30].…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…In our earlier study, we have reported higher oxidative stress indicated by the increased MDA levels in all regions of preterm preeclampsia group as compared to the normotensive control group [24]. Studies from our department and by others suggest that there is a presence of higher oxidative stress in women with preeclampsia and in preeclampsia placenta [29,30].…”
Section: Discussionmentioning
confidence: 49%
“…In addition, we have also reported increased oxidative stress in the central maternal region as compared to central fetal region in the women with preeclampsia delivering preterm [24].…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations